Potential diagnostic markers and therapeutic targets for periodontitis with comorbid infective endocarditis based on bioinformatics and experimental analyses - Mei, Feng; Zhang, Wenjie; Wang, Xinlin; Liu, Yutong; Zhou, Xiangyu; Zhou, Ting; Zhang, Wei (Frontiers in Cell and Developmental Biology, 2025)
BackgroundPeriodontitis (PD) and infective endocarditis (IE) significantly impair quality of life and contribute to considerable socioeconomic burdens. Accumulating evidence supports a bidirectional interaction between these diseases that aggravates clinical outcomes. This study aims to identify diagnostic biomarkers and investigate therapeutic targets underlying PD-IE comorbidity.MethodsWe analyzed disease-specific differentially expressed genes (DEGs) for PD and IE from datasets in the Gene Expression Omnibus (GEO). Functional enrichment analysis was then performed to investigate the biological roles of the DEGs in PD and IE datasets. Protein-protein interaction (PPI) networks were constructed using STRING database and hub genes were identified utilizing cytoHubba plugin in Cytoscape software. We selected diagnostic markers using a dual-algorithm approach that combined differential expression analysis and receiver operating characteristic (ROC) curve analysis, and subsequently evaluated their immune associations and therapeutic relevance. Our key findings were further validated using in vivo PD models.ResultsA total of 22 DEGs were identified as common to both PD and IE. PPI analysis uncovered five hub genes. ROC curve analysis supported the diagnostic utility of these five markers. Following expression analysis, we identified 4 hub genes as potential diagnostic markers: ITGAM, FCGR3B, FCGR3A and ITGB2. Significant correlations were observed between the expression of these genes and immune cell infiltration in both diseases. In vivo experiments confirmed the upregulation of the potential diagnostic markers in PD tissues compared to normal controls.ConclusionITGAM, FCGR3B, FCGR3A, and ITGB2 can serve as mechanistically informative diagnostic biomarkers and promising therapeutic targets for PD-IE comorbidity. The shared pathophysiology of the two diseases involves immune response mechanisms. Our findings open up new avenues for the concurrent therapeutic targeting of both diseases.